Prostatitis‐like symptoms in Antioquia, Colombia using the National Institute of Health‐Chronic Prostatitis Symptom Index. Issue 1 (17th July 2022) - Puerta Suárez, Jenniffer; Cardona Maya, Walter Darío
Abstract: The aim of the present study is to find the frequency of chronic prostatitis in Antioquia, Colombia. There are epidemiological gaps in this issue in the Colombian population. Chronic prostatitis is a prevalent disease with a high impact on life quality. The NIH‐Chronic Prostatitis Symptom Index (NIH‐CPSI) is a commonly used 13‐item questionnaire to assess symptom severity in men with chronic prostatitis/chronic pelvic pain syndrome. A validated Spanish version of the NIH‐CPSI questionnaire was distributed through social media and institutional e‐mails from the University of Antioquia database and other institutions in the Metropolitan Area. Of the distributed questionnaires, 2022 were filled. The vast majority of participants were students, teachers, and professionals. A frequency of 16.4% chronic prostatitis symptoms was observed, 10.1% of individuals had severe symptoms with a median age of 32 years, accompanied by perineal pain and ejaculatory symptoms. Using the NIH‐CPSI, the reported worldwide prevalence of chronic prostatitis is range between 1.8% and 65%. This report shows the disease's frequency in Colombia and Latin America for the first time. Chronic prostatitis is a frequent disease in the Antioquia population, with a high impact on the quality of life. Therefore, public health policies should be implemented focusing on men's health.